STUDI KOMPARATIF METODE IJTIHAD MAJELIS ULAMA INDONESIA DAN BAHTSUL MASAIL NAHDLATUL ULAMA TENTANG FATWA VAKSIN ASTRAZENECA - Anisah Alkatiri; Idaul Hasanah; R. Tanzil Fawaiq Sayyaf (Asy-Syari'ah, 2022)
This paper aims to compare the ijtihad methods used by the Indonesian Council of Ulema (MUI) and Bahtsul Masail Nahdlatul Ulama concerning the fatwa on the AstraZeneca COVID-19 vaccine. The study method is qualitative, with a normative legal approach and descriptive-comparative analysis. According to the findings of this study, MUI employs the type of ijtihad jama'iy (collective ijtihad) and interdisciplinary by using ijtihad bayani, ta'lili, and istishlahi methods in its ijtihad on the AstraZeneca vaccine. MUI declared in its fatwa that the AstraZeneca vaccine's legal origin is haram since it comes into touch with a haram substance or unclean during the production, namely trypsin which is produced from pig pancreas. However, the use of the AstraZeneca vaccine is temporarily permitted due to several reasons. While Bahtsul Masail in their ijtihad employs the type of ijtihad jama'iy and interdisciplinary ijtihad using the qauly and ilhaqy ijtihad methods. In their conclusion, Bahtsul Masail declared that the AstraZeneca vaccine is permissible to use under normal circumstances, particularly in an emergency, not only because it is safe but also because it is holy. However, in issuing a fatwa on the Covid-19 vaccine for AstraZeneca products, both MUI and Bahtsul Masail are pursuing the same goal: saving human lives (hifz al-nafs), and both institutions' decisions are based on reasonable and empirical considerations in the context of the public good, expecting that herd immunity would be achieved shortly in Indonesia, permitting it to be free from the Covid-19 pandemic quickly.